Young settlers's political education and their relation to field school - Joarez Luiz Wegher; Suely Aparecida Martins (Universidade Federal do Norte do Tocantins, 2020)
The present article presents some results of a Master's degree research on the contributions of Paulo Freire State High School along the process of political education of young settlers who lives in the municipality of Abelardo Luz, in the Brazilian state of Santa Catarina. It aims to identify this school's contributions in the process of political education of these young people and understand the relation between such a formation and the struggle for a field school. This qualitative study used as tools for collecting data school observations, analysis over its political-pedagogical project, and semi-structured interviews. We based our analysis on authors such as Pistrak (2000; 2009), Freire (1987; 2004), Snyders (2005), Dalmagro (2003; 2016), Vendramini (2007) and Caldart (2000; 2004). Paulo Freire school is contextualized along with the research subjects, students' and educators' characteristics, highlighting some contributions given to the school in connection to the political education of its students. One of the conclusion is that the participation of the Landless Movement and school takes place according to the political-pedagogical project based on Study Complexes, contributing to the fulfillment of a field school when it reaffirms a school formation as a right and reinforces the permanent need of school occupation. It is reinforced the school as a room for struggles, a terrain where contradictory forces face each other, leaving room for action.